Contraception options: Aspects unique to adolescent and young adult. (April 2018) - Apter, Dan
Abstract: Sexual health for adolescents is based on three components: recognizing sexual rights, sexuality education and counseling, and thirdly confidential high quality services. Contraception needs to include prevention of both STIs and pregnancies. The first option for adolescents is condoms backed-up by emergency contraception; and later hormonal contraceptives in a longer, mutually monogamous relationship. Condoms and hormonal contraception together can be well recommended for adolescents for dual protection. Long acting reversible contraception (LARC) including both intrauterine contraception and implants are safe and highly effective and thus well suited for adolescents. Improved contraceptive methods do not automatically lead to reduced numbers of adolescent abortions. When sexuality education, proper counseling and sexual health services are all provided, it is possible to profoundly improve adolescent sexual health. Highlights: Long acting reversible contraception such as intrauterine contraception and implants have much higher contraceptive efficacy, are safe also for adolescents, and should be recommended. Counselling is the central part of providing contraception for adolescents, pelvic examination is needed only prior to inserting IUC, and not when prescribing COC. Quick start on any menstrual cycle day is possible for pills, rings, patches and implants, as well as Cu-IUD and LNG-IUS if it is reasonably certain that the patient is not pregnant. Cu-IUD is the most effective method of emergency contraception. Ulipristal acetate is more effective than levonorgestrel and works for 5 days.